A new species of Chalybea (Blakeeae, Melastomataceae) from the Ecuador-Peru border - Ulloa Ulloa, Carmen; Penneys, Darin S.; Neill, David A.; Fernandez, Diana M. (Phytotaxa, 2015)
A new species, Chalybea brevipedunculata, from the Ecuador-Peru border is herein described and illustrated. It differs from all other species in the genus by having inflorescence peduncles that are shorter than their subtending leaf petioles.